Growth and Raman Scattering Investigation of a New 2D MOX Material: YbOCl. (16th August 2019) - Yao, Yuyu; Zhang, Yu; Xiong, Wenqi; Wang, Zhenxing; Sendeku, Marshet Getaye; Li, Ningning; Wang, Junjun; Huang, Wenhao; Wang, Feng; Zhan, Xueying; Yuan, Shengjun; Jiang, Chao; et al.
Abstract: MOX (M = Fe, Co, Mn, Cr, Lanthanide, or Actinide metals; O = oxygen, X = F, Cl, Br, I), an emerging type of 2D layered materials, have been theoretically predicted to possess unique electronic and magnetic properties. However, 2D MOX have rarely been investigated. Herein, for the first time, ultrathin high‐quality ytterbium oxychloride (YbOCl) single crystals are successfully synthesized via an atmospheric pressure chemical vapor deposition method. Both theoretical simulations and experimental measurements are utilized to systematically investigate the Raman properties of 2D YbOCl nanosheets. The experimentally observed Eg mode at 85.53 cm −1 and A1g mode at 138.17 cm −1 demonstrate a good match to the results from density functional theory calculations. Furthermore, the temperature‐dependent and thickness‐dependent Raman scattering spectra reveal the adjacent layers in YbOCl nanosheets show a relatively weak van der Waals interaction. Additionally, the polarized‐dependent Raman scattering spectra show the intensity of A1g mode exhibits twofold patterns while the intensity of the Eg mode remains constant as the rotation angle changes. These findings could provide the first‐hand experimental information about the 2D YbOCl crystals. Abstract : The controllable synthesis of high‐quality two‐dimensional (2D) ytterbium oxychloride (YbOCl) nanosheets is demonstrated. High‐resolution transmission electron microscopy and selected‐area electron diffraction reveal its high crystal quality and single‐crystalline structure. The systematic Raman scattering spectra of YbOCl single crystals from both experimental and theoretical perspectives are studied.